Analysis of Dirty Adapters and Dirty Connectors on Fiber Optic Transmission - Farhan, Muhammad Fachrel; Popy Maria; Amelia Yolanda; Aprinal Adila Asril (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2024)
The author conducts research on dirty adapters and dirty connectors in fiber optic transmission to determine the value or attenuation that will be produced due to the influence of dirty adapters and dirty connectors. This study was conducted to evaluate the attenuation value due to dirty adapters and dirty connectors in fiber optic transmission before and after the use of Passive Splitter 1: 16. The method used includes the initial step of calibration between the Optical Power Meter (OPM) and Handheld Light Source (HLS). The HLS was connected to the first Optical Distribution Point (ODP) with a patch cord cable to provide attenuation, and data was taken at the second ODP using the OPM. The power data received on the unproblematic core (gray) without the 1:16 Passive Splitter was 0.65 dB, while with the 1:16 Passive Splitter the attenuation increased to 13.71 dB. The red dirty adapter causes 5.99 dB of attenuation without the Passive Splitter 1:16 and 19.21 dB with the Passive Splitter 1:16. The brown dirty connector exhibits an attenuation of 4.68 dB without the Passive Splitter 1:16 and 19.08 dB with the Passive Splitter 1:16. These findings suggest that the physical condition and cleanliness of the components significantly impact the attenuation in the fiber optic network.